Nonlinear Vibration Analysis of Bearing-Rotor Systems with Ball Defects Considering Time-Varying Displacement Excitation - Wang, Hui; Su, Zhenning; Liu, Chang; Meng, Fancheng; Song, Bo; Zhang, Shiying (Scientific Journal of Technology, 2026)
Bearing-rotor systems are of critical significance to advanced rotating equipment. However, under high-speed operating conditions, defects may occur on the ball surfaces due to increased contact stresses. To understand the influence of ball surface defect on the bearing-rotor systems, the time-varying displacement excitation is proposed. Defect size changes contact deformation in the bearing. The contact force is changed as a result. These factors are incorporated into the dynamic model. The model describes a bearing-rotor system with a defect-ball bearing. Bifurcation diagrams is employed, the influence of speed and defect dimensions on the system’s nonlinear vibration is examined. Experimental validation is conducted through vibration testing. The results show that the occurrence of ball defects has a notable effect on the system’s motion behavior. With the increase in the size of ball defects, the amplitudes of the relevant frequencies fb, fc and their combined frequencies in the spectrum increase. Strong alignment is seen between experimental and simulated outcomes, and the amplitude error of the ball impact frequency is 4.9%. This study provides a framework for analyzing the dynamics of bearing-rotor systems.